End of Meeting Report - ISPC 16 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
The ISPC holds two open meetings per year to report on ongoing activities in each of its five workstreams. The 16th meeting of the ISPC took place at ICARDA Offices in Rabat, Morocco, from 18-19 September 2017.